Job satisfaction survey among health centers staff - Shahnazi, Hossein (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Due to the importance of health care organizations with significant responsibility for prevention and care, assessment of job satisfaction among health care staff is essential. Quality of health services will be decreased provided they are not satisfied. MATERIALS AND METHODS: This study was a cross-sectional analysis of health care staff in Khomeinishahr (centers, buildings, and networks) If they had at least 6 months work experience, they could enter the study. Data included a two-part questionnaire with a standardized questionnaire, demographic variables, and Smith job descriptive index, which is a questionnaire with six domains. Reliability was obtained for each domain and its validity was reported 0.93. FINDINGS: The results showed an overall satisfaction score averages 43.55 ± 12.8 (from 100). Job satisfaction score was not significantly different between the sexes. However, within the current attitude toward job satisfaction, men scores was better than women (P = 0.001). Highest score in job satisfaction was related to relationships with colleagues and lowest score was related to the income, benefits, and job promotion. The more the years of work, the less the job satisfaction was. The attitude toward the current job had a direct relationship with income (P = 0.01). There was a significant inverse relationship between educational level and job satisfaction in domains promotion, income, and benefits (P = 0.01). The staff with higher education levels was less satisfied with income and job promotion qualification. CONCLUSION: Managers should focus on job qualification to increase job satisfaction and improve the quality of work.